TiO2 nanotube-containing glass ionomer cements display reduced aluminum release rates - Ana Mara da Silva MORAIS; Ysadora Mayara Reali PEREIRA; Isaac Jordão de SOUZA-ARAÚJO; Daniel Furtado SILVA; Vanessa Gallego Arias PECORARI; Orisson Ponce GOMES; Francisco Humberto NOCITI-JÚNIOR; Regina Maria PUPPIN-RONTANI; Waldemir Francisco VIEIRA-JUNIOR; Paulo Noronha LISBOA-FILHO; Kamila Rosamilia KANTOVITZ (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract Titanium dioxide nanotubes (TiO2-nts) were incorporated into a glass ionomer cement (GIC) with improved mechanical properties and antibacterial activity. The aims of the present in vitro study were to define the elemental characterization, aluminum (Al) release rate, and initial working time for GIC reinforced with TiO2-nts, in an experimental caries model. TiO2-nts were incorporated into GIC powder components at 5% by weight, and compared with unblended GIC. Experimental approaches used energy-dispersive spectrometry (EDS), atomic absorption spectrophotometry (AAS), and brightness loss to define surface element properties, Al release rates, and initial working time, respectively. Statistical analysis was performed by 2-way ANOVA, Tukey's test, generalized linear models, and Student's t test (a = 0.05). EDS data analysis revealed that TiO2-nts incorporated into GIC had no significant impact on the typical elemental composition of GICs in an in vitro caries model. Regarding the demineralizing solution, GIC with TiO2-nt significantly decreased the Al release rate, compared with the control group (p < 0.0001). Moreover, TiO2-nt incorporated into GIC did not alter the initial working time of the material (p > 0.05). These findings add information to our scientific body of knowledge concerning the potential impact of TiO2-nt on the performance of conventional GICs.